2016
DOI: 10.1108/lhtn-09-2015-0063
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of information literacy programmes in public libraries

Abstract: Purpose The purpose of this study is to examine the implementation of information literacy programmes in the public libraries in Kenya as demonstrated through a case study of the major public library in the country – Kenya National Library Service (KNLS). Design/methodology/approach The use of a case study research design made it possible to establish in-depth personal views, opinions and attitudes of the various respondents through face-to-face interviews and questionnaires. Both quantitative and qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…One of a librarian's responsibilities is to encourage library users to achieve information literacy so that they may become lifelong learners (Agee, 2005). In order to achieve this, Kingori et al (2016) and Perry (2014) have identified the need for information literacy instruction in public libraries to foster the lifelong learning of their communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of a librarian's responsibilities is to encourage library users to achieve information literacy so that they may become lifelong learners (Agee, 2005). In order to achieve this, Kingori et al (2016) and Perry (2014) have identified the need for information literacy instruction in public libraries to foster the lifelong learning of their communities.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the international studies have investigated information literacy in public libraries (e.g. Harding, 2008;Ireland, 2017;Jacobsen, 2017;Julien and Hoffman, 2008;Kingori et al, 2016;Matteson and Gersch, 2019;Nielsen and Borlund, 2011;Widdowson and Smart, 2013). The results of these studies revealed that some public libraries offered information literacy instruction and the users of these libraries participated in the programmes offered for their information needs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite huge investment and sensitization on usage of electronic resources, instances of inadequate utilization still abound, partly due to lack of relevant adequate skills that can be applied in the networked environment (Waithaka, 2013). This is despite concerted efforts by universities to sensitize every new student on access and use of electronic resources through orientation programmes (Muhia, 2015;Kingori, Njiraine & Maina, 2016). Several studies have delved into issues of internet usage, more so on usage of electronic resources and their relevance to the students often as separate studies and have variously reported their inadequate utilization for academic purposes (Boakye, 2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The number of public library publications increased this year. Topics included the importance of information literacy, as expressed in "A Rationale for Public Library Civics Instruction" (Critcher Lyons, 2016) which explains the need for civics instruction in school and public libraries, and "Implementation of Information Literacy Programmes in public libraries" (Kingori et al, 2016) which discusses a study of Kenyan libraries and the need for IL programs. In addition, the book Creating and Promoting Lifelong Learning in Public Libraries: Tools and Tips for Practitioners (Gilton, 2016) also addresses the topic of IL in libraries.…”
Section: Library Instruction and Informationmentioning
confidence: 99%
“…study are explained, and the article determines that it is important to continue the focus on information literacy given its "misunderstanding" among some students. Kingori, G., Njiraine, D. and Maina, S. (2016), "Implementation of information literacy programmes in public libraries", Library Hi Tech, Vol. 34 No.…”
Section: Library Instruction and Informationmentioning
confidence: 99%